An automatic rempeyek machine / Siti Nur Aina Khadijah Mohd Noh and Siti Khadijah Alias - Mohd Noh, Siti Nur Aina Khadijah; Alias, Siti Khadijah (School of Mechanical Engineering, 2023)
Rempeyek is one of the most popular traditional snacks in Malaysia. However, the process of making Rempeyek needs to be done individually and manually step by step. It requires a lot of energy, time, and cost. In addition to that, an automatic Rempeyek machine is being made to speed up the process so there will be a lot of Rempeyek produced with the same quality, taste, and texture at a certain time. This project requires design skills, dynamic theories, selection of the right materials that can be used, a lot of research, and study of other similar machines to understand properly the mechanism used. At the end of the project, the automatic Rempeyek machine needs to function properly. The moving mechanism of the molding plate should move properly, and the frying compartment must supply the right amount of heat needed for the oil to boil. In conclusion, this automatic Rempeyek machine will be a greater help for those who need it such as the small industries or seller who sell Rempeyek to be able to use a much easier method in making Rempeyek without spending too much money as the cost of the machine is still at affordable level.